On the status of the genus Hybochilus, with a new combination in Leochilus (Orchidaceae: Oncidiinae) - Pupulin, Franco (2021)
The name Rodriguezia inconspicua, proposed as a replacement name for Trichocentrum candidum, is a homotypic synonym of the latter, as well as the new combinations based on the same name. The genus Hybochilus, typified by Rodriguezia inconspicua, is reduced into synonymy under Trichocentrum. A new combination, Leochilus candelariae, is proposed to accommodate the species from Costa Rica. Rodriguezia candelariae is typified.